Nutrition and Fertilization Practices for Southern Highbush Blueberry in Florida - Doug Phillips; Jeffrey G. Williamson (EDIS)
Research and field experience have demonstrated that fertilization is necessary to achieve proper growth and high yields in cultivated production of blueberries. This new 7-page publication of the UF/IFAS Horticultural Sciences Department provides guidance and management suggestions to Florida growers of southern highbush blueberry (SHB) for monitoring, supplying, and maintaining proper plant nutrition in commercial production operations. Written by Doug Phillips and Jeffrey G. Williamson. https://edis.ifas.ufl.edu/hs1356